The 30 October 2020, M7.0 Samos Island (Eastern Aegean Sea) Earthquake: effects of source rupture, path and local-site conditions on the observed and simulated ground motions - Akinci, A.; Cheloni, D.; Dindar, A. A. (Springer, 2021)
On 30 October 2020 a M-W 7.0 earthquake occurred in the eastern Aegean Sea, between the Greek island of Samos and Turkey's Aegean coast, causing considerable seismic damage and deaths, especially in the Turkish city of Izmir, approximately 70 km from the epicenter. In this study, we provide a detailed description of the Samos earthquake, starting from the fault rupture to the ground motion characteristics. We first use Interferometric Synthetic Aperture Radar and Global Positioning System data to constrain the source mechanisms. Then, we utilize this information to analyze the ground motion characteristics of the mainshock in terms of peak ground acceleration (PGA), peak ground velocity, and spectral pseudo-accelerations. Modelling of geodetic data shows that the Samos earthquake ruptured a NNE-dipping normal fault located offshore north of Samos, with up to 2.5-3 m of slip and an estimated geodetic moment of 3.3 x 10(19) Nm (M-W 7.0). Although low PGA were induced by the earthquake, the ground shaking was strongly amplified in Izmir throughout the alluvial sediments. Structural damage observed in Izmir reveals the potential of seismic risk due to the local site effects. To better understand the earthquake characteristics, we generated and compared stochastic strong ground motions with the observed ground motion parameters as well as the ground motion prediction equations, exploring also the efficacy of the region-specific parameters which may be used to better predict the expected ground shaking from future large earthquakes in the region.
Keywords: Earthquake source observations; Satellite geodesy; Ground motions simulations; Site effects; Building damage distribution; Eastern Aegean Sea earthquake